2024
DOI: 10.1037/cps0000158
|View full text |Cite
|
Sign up to set email alerts
|

Is the use of interpretations associated with treatment outcome? A systematic review and meta-analytic answer.

Sigal Zilcha-Mano,
John R. Keefe,
Hadar Fisher
et al.

Abstract: Interpretation is the doyen of therapeutic techniques and has received some of the greatest theoretical and clinical attention. Nevertheless, to date, no meta-analysis has examined its effect on psychotherapy outcome. In the present systematic review and meta-analysis, we examined the association between interpretations and psychotherapy outcome. The meta-analysis was preregistered in PROSPERO. From 13,195 initially identified abstracts, we extracted 16 independent effect sizes from a total of 897 patients. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…However, with some patients, relationship issues are more important, while in others, interpretative techniques are most relevant. It is important to remember that Zilcha-Mano et al (2023) found that the association between the utilization of interpretations and outcome is comparable to the association between therapeutic alliance and outcome.…”
Section: The Clinical Impact Of This Studymentioning
confidence: 96%
See 2 more Smart Citations
“…However, with some patients, relationship issues are more important, while in others, interpretative techniques are most relevant. It is important to remember that Zilcha-Mano et al (2023) found that the association between the utilization of interpretations and outcome is comparable to the association between therapeutic alliance and outcome.…”
Section: The Clinical Impact Of This Studymentioning
confidence: 96%
“…However, with some patients, relationship issues are more important, while in others, interpretative techniques are most relevant. It is important to remember that Zilcha-Mano et al (2023) found that the association between the utilization of interpretations and outcome Leon Hoffman https://orcid.org/0000-0001-7466-5513 I thank the editors for allowing me to discuss this very important paper by Sigal Zilcha-Mano, John R. Keefe, Hadar Fisher, Tohar Dolev-Amit, Nirit Veler-Poleg, and Jacques P. Barber.…”
Section: The Clinical Impact Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been many reviews and theoretical articles on the role of interpretation in psychotherapy, this is the first meta-analysis examining the association between interpretations and treatment outcome (Zilcha-Mano et al, 2023). Rigorous standards for conducting meta-analyses were stringently followed, with findings derived from a relatively small sample of 16 studies with 897 patients in total.…”
mentioning
confidence: 99%
“…However, the context, specificity, and degree of responsiveness in interpretation require further explication. To their credit, the authors of this meta-analysis suggest that future studies need to “explore in greater depth for whom interpretations should be more intensely used, by whom, and when” (Zilcha-Mano et al, 2023, p. 18). The authors also point out that future research should examine patient characteristics, the quality of interpretations, their accuracy, and responsiveness as potential moderators.…”
mentioning
confidence: 99%